2005
DOI: 10.1007/s00429-004-0449-3
|View full text |Cite
|
Sign up to set email alerts
|

Mophometric study of the aortic arch and its major branches in rat fetuses on the 21st day of gestation

Abstract: The anatomy and embryology of the aortic arch and its branching tributaries (brachiocephalic trunk, left common carotid artery and left subclavian artery) in man and animals are well substantiated. However, the anatomical variations and morphometry of the aortic arch and its branching tributaries in rat fetus at the 21st gestation day have not been studied. Pregnant rats were hysterectomized and the arterial systems of 114 fetuses were injected with a polymerisable resin through the umbilical artery. After mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…Gielecki et al [12] reported that the formation of the arteries from the Aa is complete in the early embryonic stage, and that 80.6% of human fetuses aged between 14 to 30 weeks showed a normal pattern with the same variations in 19.6% compared with adults. Monnereau et al [19] reported that 98% of 21-day old rat fetuses had the same branching pattern as adults. The diameter and length of the Aa and its arteries are dependent on age [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gielecki et al [12] reported that the formation of the arteries from the Aa is complete in the early embryonic stage, and that 80.6% of human fetuses aged between 14 to 30 weeks showed a normal pattern with the same variations in 19.6% compared with adults. Monnereau et al [19] reported that 98% of 21-day old rat fetuses had the same branching pattern as adults. The diameter and length of the Aa and its arteries are dependent on age [19].…”
Section: Discussionmentioning
confidence: 99%
“…Monnereau et al [19] reported that 98% of 21-day old rat fetuses had the same branching pattern as adults. The diameter and length of the Aa and its arteries are dependent on age [19]. Unfortunately, there was an insufficient number of the Korean water deer to make a proper comparison according to each growth period such as suckling, weaning, growth, sexual maturation and adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, detailed anatomical descriptions of the aortic arch of the Antillean manatee are indispensable. Moreover, such descriptions may also be useful in toxicological studies, since numerous chemicals, including some drugs, may produce aortic arch malformations (Monnereau et al, ). Anatomical studies also provide information regarding the diagnosis and clinical treatment of diseases by means of complementary tests such as Doppler echocardiography and contrast radiography (Bortolini et al, ; Cabral, Ciasca, Oliveira, Vaz‐Curado, & Larsson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the species of animal, one or more arteries branch from the aortic arch. These branches in humans (Gielecki et al., ; Zamir and Sinclair, ), chimpanzees (De Garis, 1933), rats (Hebel and Stromberg, ; Monnereau et al., ), mice and hamsters (Sinzinger and Hohenecker, ) include the left common carotid artery, the left subclavian (LSb) artery and the BCT. Only the last two branches of the aortic arch has been observed in rabbits (Angell‐James, ; Baldwin, ), guinea pigs (Shively and Stump, ), pigs (Ghoshal, 1975c), dogs, cats (Ghoshal, 1975d; Rosenzweig, ) and monkeys (De Garis, , ).…”
Section: Introductionmentioning
confidence: 99%